Genotyping of Echinococcus granulosus Human Isolates Obtained from the Puncture, Aspiration, Injection, and Re-Aspiration (PAIR) Process in Türkiye - Önder Akkaş; Mesut Özgökçe; Selahattin Aydemir; İlyas Dündar; Abdurrahman Ekici (Iranian Journal of Parasitology, 2023)
Background: Echinococcus granulosus is spread by the excretion of cystic organs into the environment. The dog is infected via eating the cystic organ. It then contaminates the environment with eggs of E. granulosus, which are infective to humans and animals. We aimed to determine the E. granulosus genotypes that cause infection in humans in the Van region, Türkiye.